Offshore Exploration of Oil and Gas in Cuba using Digital Elevation Models (DEMs) - Pardo Echarte, Manuel Enrique (SpringerBriefs in Earth System Sciences,, 2018)
This book provides an overview of the major changes induced by hydrocarbons (HCs) affecting rocks and surface sediments and their implications for non-seismic exploration methods, particularly for marine territories near Cuba. It examines the use of a digital elevation model (DEM) at 90x90m resolution for the detection of subtle, positive geomorphic anomalies related to hydrocarbon microseepage (vertical migration) on possible oil and gas targets. The results support the conclusion that the DEM data provides a low cost and fast offshore oil and gas preliminary exploration strategy. This data is useful serving to focus prospective areas with supplementary unconventional methods such as magnetic-induced polarization (MIP), useful to propose more expensive volumes for detailed 2D-3D seismic surveys. .